Cytotoxic Effector Cells from Infectious Mononucleosis Patients in the Acute Phase Do Not Specifically Kill Epstein-Barr Virus Genome-Carrying Lymphoid Cell Lines - Patel, Pravin C. (Infect Immun, 1982)
We describe a study in which we investigated the cytotoxic activities of thymusderived (T) lymphocytes and natural killer cells against Epstein-Barr virus (EBV) genome-carrying lymphoid cell lines. Purified subpopulations of lymphocytes from eight patients with infectious mononucleosis and six healthy normal EBV-seropositive donors were tested. Enriched T-cells were obtained by passing purified whole blood lymphocyte preparations through human immunoglobulin-anti-immunoglobulin-coated glass bead columns. The cytolytic activity of effector cells was determined by the ability of these cells to lyse human target cells that were internally labeled with (51)Cr. These targets included cells from both EBV genome-carrying and EBV genome-negative lymphoid lines derived from malignant tumors, as well as from lymphocytes transformed in vitro by EBV, and were chosen to represent a wide spectrum of EBV-associated membrane antigens. We found that cytotoxic T-cells from patients with infectious mononucleosis showed no EBV-related specific cell killing per se, although a trend for increased killing of cell lines derived from spontaneous in vivo growing tumors, EBV genome carrying or not, was noted; however, this trend was not observed with cell lines derived from cord blood lymphocytes after EBV infection in vitro. In addition, our data suggest that natural killer cells may play an important role in controlling EBV infection in patients with infectious mononucleosis in the acute phase of the disease, particularly since T-cells (obtained after removal on immunoglobulin-anti-immunoglobulin columns of natural killer cells presumably bearing Fc receptors) were less efficient killers than whole blood lymphocytes; furthermore, lysis by whole blood lymphocytes was also greatest against cell lines derived from malignant tumors (as opposed to in vitro EBV-transformed cord blood lymphoid lines), irrespective of whether these targets were EBV genome positive or negative.